A GESTÃO ESCOLAR EM FOCO: REFLEXÕES PRELIMINARES - Elisangela Aparecida Bulla Ikeshoji; Adriana Aparecida de Lima Terçariol; Adriano Rodrigues Ruiz (Universidade do Oeste Paulista, 2015)
In school management should be geared to meet the fundamental aspect, education. Essential for the human being, the subject of his own training. From this perspective, this paper has as main purpose to analyze the role of the manager and managing the educational institution as well as discuss culture as part of this process. To this end, a literature search was triggered, taking as a reference work by renowned authors in the field. The main result of this exploratory study offered support for planning for deeper analysis, in which researchers will develop a qualitative approach, the case study type, next to the Post-Graduate Education - MSc - University of the West Paulista (UNOESTE), with the purpose of revealing, through the technique of the Collective Subject Discourse (CSD), as the manager and teachers understand the management and position themselves on the subject.